Cytotoxic Activity of Aporphine Alkaloids from Alseodaphne Peduncularis (Wall. Ex. Ness) Meissn against Hela Cell Line - Ulil Amna; Kartini Ahmad; Mohd Azlan Nafiah (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2015)
Genus of Alseodaphne has been known as a source of apoprhine alkaloid that displayed potent cytotoxic activities against selected cell lines. Two aporphine alkaloids, Corydine 1 and norlirioferine 2 were isolated from leaves of Alseodaphne peduncularis (Wall. Ex. Ness) Meissn. (Lauraceae). Phytochemical study involved extraction, separation and purification by using various chromatography methods and structural elucidation by using spectoscopic techniques such as UV, IR LC-MS and 1D and 2D NMR. These compounds were then assayed for cytotoxicity against human uteric cervical tumor (heLa) and compare for safety with normal mouse fibroblast (NIH/3T3) cell lines by using the MTT assay. Compound 2 displayed potent cytotoxic activities against heLa cell, but compound 1 showed as inactive. Both compounds have no significant effect against NIH/3T3 cell lines indicated good for cancer agent treatment.